Allelopathic effect of aqueous extracts from agro-industrial residues of pecan nut [Carya illinoinensis (Wangenh) C. Koch] and pinhão (Araucaria angustifolia) - SANT'ANNA, Voltaire; KLEIN, Maico Ismael; BIONDO, Elaine; KOLCHINSKI, Eliane Maria (Revista Eletrônica Científica da UERGS, 2017)
Pinhão seed coat and pecan nutshell are residues widely produced in households and industries, which present great potential to be used as source of natural preservatives in the food chain. The objective of the present study is to evaluate the effectiveness of pinhão seed coat and pecan nutshell aqueous extracts in inhibiting seed germination. Extracts were obtained in concentration of 10g/L, 5g/L and 2.5g/L and tested against lettuce seed germination in vitro tests. The results show that both aqueous extract presented the significant (p<0.05) ability to inhibit seeds germination as well as the germination seed index, in relation to control experiments, when used in concentrations of up to 5g/L. Extracts did not interfere significantly (p>0.05) the germinated plant root size. Thus, aqueous extracts of agro-industrial residues from pinhão seed coat and pecan nutshell presents alellopathic activity, showing up as interesting alternative to be used as natural herbicide, also representing a way of solid waste management by industries and small farmers.